Visual Outcome of Unilateral Paediatric Traumatic Cataract at R. M. Kedia Eye Hospital, Birganj, Nepal - Singh, Sanjay; Sah, Harikant; Keyal, Amar (Journal of College of Medical Sciences-Nepal, 2016)
Background & Objectives: To evaluate the visual outcomes of children presenting with unilateral traumatic cataract. Materials & Methods: We conducted a retrospective study of 111 children (70 males and 41 females) below 16 years of age who were diagnosed with unilateral traumatic cataract between June 2013 and May 2015 and who underwent surgical intervention and completed at least six months follow up at Paediatrics department (supported by ORBIS International), R. M. Kedia eye hospital, Birganj, Nepal. Data regarding demographic profile, causative agent, clinical course and visual outcomes were recorded. Results: There was a male predilection with a male to female ratio of 1.70:1. The age group more frequently affected was five to nine years (58.5%). Commonest causative agent was trauma with wooden stick in 20 eyes (18%) followed by firecrackers in 15 eyes (14%) and pen in 11 eyes (10%). Pre-existing posterior capsular defects were observed intraoperatively in six eyes. Anterior uveitis was evident in 21 cases and Posterior capsular opacification in 10 eyes. Best corrected visual acuity of 6/6-6/60 at six months was achieved in 91 cases (81%). Duration between injury and cataract surgery did not affect the final visual outcome of traumatic cataract patients. Conclusion: The best possible visual outcome of traumatic cataract depends on its management and its complication. Ocular trauma and traumatic cataract formation can be avoided by taking protective measures in sports, work and patient education. JCMS Nepal. 2016;12(2):40-3